Desigualdades educativas y socioespaciales en la educación secundaria en Argentina: aportes para la identificación de circuitos educativos en los departamentos de la provincia de Chaco - Sassera, Jorgelina Silvia (Universidad Nacional del Litoral, 2022)
Socio–educational segmentation is evidenced in the formation of circuits, paths or groups of educational institutions with distinct characteristics to which social classes have unequal access. The present article explores educational circuits of secondary education with a territorial perspective in the Argentine province of Chaco, and proposes to go further in studying educational inequalities with the greatest disintegration at at national, regional and provincial levels. Circuits are indentified according to the socioeconomic characteristics of students, their previous education disparities, and schooling material conditions. To this end, data from different national and provincial sources were articulated and studied through a multidimensional analysis. The analysis allowed recognizing students who access five educational circuits, segregation existence according to socioeconomic level, school access and retention in secondary education, and inequality in learning achievements. An approach to identifying the location of these circuits by provincial departments made it possible to explore the relationship between the living conditions in each area and greater or smaller material advantages of secondary schools.